EDUKASI EKONOMI HIJAU DALAM MENUMBUHKAN SEMANGAT “GREEN ENTREPRENEURSHIP” - Arum Ardianingsih; Feby Meliana (LPPM Universitas Pekalongan, 2021)
Green economy education is an effort to provide information to other people to know and understand environmentally friendly business activities. Limited natural resources due to environmental damage sometimes lead to creative ideas to start a business or business. Community service activities are carried out through education with outreach methods to the community in the Bandengan sub-district, North Pekalongan sub-district. The result of this service activity is that public knowledge and understanding of the green economy increases and fosters the spirit of starting a business by utilizing limited natural resources due to the tidal flood disaster.Keywords: Green Economy, Entrepreneur, Bandengan.